Pelatihan Penyusunan Anggaran Berbasis Kinerja dan Kerjasama Tim Karyawan Klinik Sari Medika Ambarawa - Dian Prawitasari; Sih Darmi Astuti; Ana Kadarningsih (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Sari Medika Ambarawa Clinic is a company in the health sector with service as the key to company performance. Problems that occur at the Sari Medika Ambarawa Clinic include difficulties in determining the next budget period, resulting in shortages of medicines and goods which can reduce the profits of the Sari Medika Ambarawa Clinic. Apart from that, another problem is the lack of cooperation between employees which causes relations between employees to become less solid and harmonious. Training on budget preparation and collaboration between employees is training that is right on target in solving problems that occur at the Sari Medika Ambarawa Clinic. There are four stages in this training, namely the lecture stage, question and answer stage, discussion stage and simulation or practice stage. The results of the training showed that employees from division nine were able to make a budget per division for the next period. Meanwhile, the results of collaboration training between employees have made Sari Medika Ambarawa Clinic employees more enthusiastic about working and relationships between employees have become solid and harmonious.